ҚУСЛАРДЫӉ БЕЛГИЛЕРИНИӉ ПАЙДА БОЛЫЎЫ ҲАҚҚЫНДА ҚАРАҚАЛПАҚ ҲӘМ ҚАЗАҚ ЭТИОЛОГИЯЛЫҚ ӘПСАНАЛАРЫ - Жуманазарова, Г.Д. (FAN va JAMIYAT, 2025)
In this article the appearance of features of some birds in the folklore legends of the Karakalpak and Kazakh people and their etiology are widely discovered based on research. Also the significance, similarities, and essence of legends in the folklore of the Karakalpak and Kazakh folks are discussed.